SISTEM INFORMASI PELAYANAN DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN BATANG HARI BERBASIS WEBSITE: Rescue Service;A Fire Occurs;Telephones;Fast and Easy;Fire Department. - Elzas; Huda Aminuddin, Fattachul; Minarsih, Mega (LP2M Universitas Nurdin Hamzah, 2022)
The Batang Hari Fire and Fire Department, which serves the community and helps the community when a fire occurs, the current complaint process is a manual complaint system, which uses telephones to report fire incidents. The purpose of this research is to produce information that is fast and easy to obtain for the community and the Batanghari fire department. This application-based community complaint information system for firefighters uses the PHP programming language. In this study, the system development method used in this study is SDLC (System Development Life Cycle) with the waterfall model method. The stages in the SDLC include, literature study, data collection, problem identification, system design, and implementation.After being tested, it can be seen that in general this system can overcome the problems found in the community and the fire department. So that in general this system can provide solutions to users and the system runs as expected.